Effect of the compatibilizer on the physical properties of biaxially deformed in situ composites - Seo, Y; Kim, J; Kim, HJ (SOC PLASTICS ENG INC, 2002)
The effect of a compatibilizer (poly(ester imide), PEsI) on the biaxial deformation of a thermotropic liquid crystalline polymer (TLCP, poly(ester amide)) in a poly(ether imide) and the properties of biaxially deformed in situ composites were studied. The compatibilizer improved dispersion of the TLCP and the adhesion between TLCP and the matrix. The properties of blown films were affected by the amount of the compatibilizer used. The morphology evidently shows that ca. 0.6 wt% PEsI provides the best morphology when 10 wt% VB phase is included. The mechanical properties, especially in the hoop direction, were significantly improved for the compatibilized films compared to uncompatibilized one. The impact strength of a compatibilized blend film with 0.6 wt% PEsI was almost twice that of an uncompatibilized blend film.
Keywords: LIQUID-CRYSTALLINE POLYMER; TLCP TERNARY BLENDS; FUNCTIONALIZED POLYPROPYLENE; MECHANICAL-PROPERTIES; THERMOPLASTIC ELASTOMER; POLY(ESTER AMIDE); MORPHOLOGY; FLOW; BEHAVIOR; NYLON-6